Educational Antenna Traning Set for Radiation Pattern Plotting and Analysis Using Basic Antenna Shapes - Azremi, Abdullah Al Hadi; Soh, Ping Jack; Dayang Khadijah, Hamzah; R. Badlishah, Ahmad, Assoc. Prof. Dr. (Malaysian Invention and Design Society (MINDS), 2010)
Azremi Abdullah Al-Hadi and his team from School of Computer & Communication Engineering won silver for Educational Antenna Traning Set for Radiation Pattern Plotting and Analysis Using Basic Antenna Shapes. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.